Inhibition of homocysteine-induced endoplasmic reticulum stress and endothelial cell damage by l-serine and glycine. (August 2016) - Sim, Woo-Cheol; Han, Inhoi; Lee, Wonseok; Choi, You-Jin; Lee, Kang-Yo; Kim, Dong Gwang; Jung, Seung-Hwan; Oh, Seon-Hee; Lee, Byung-Hoon
Abstract: Hyperhomocysteinemia is an independent risk factor for several cardiovascular diseases. The use of vitamins to modulate homocysteine metabolism substantially lowers the risk by reducing plasma homocysteine levels. In this study, we evaluated the effects ofl -serine and related amino acids on homocysteine-induced endoplasmic reticulum (ER) stress and endothelial cell damage using EA.hy926 human endothelial cells. Homocysteine treatment decreased cell viability and increased apoptosis, which were reversed by cotreatment withl -serine.l -Serine inhibited homocysteine-induced ER stress as verified by decreased glucose-regulated protein 78 kDa (GRP78) and C/EBP homologous protein (CHOP) expression as well as X-box binding protein 1 ( xbp1 ) mRNA splicing. The effects ofl -serine on homocysteine-induced ER stress are not attributed to intracellular homocysteine metabolism, but instead to decreased homocysteine uptake. Glycine exerted effects on homocysteine-induced ER stress, apoptosis, and cell viability that were comparable to those ofl -serine. Although glycine did not affect homocysteine uptake or export, coincubation of homocysteine with glycine for 24 h reduced the intracellular concentration of homocysteine. Taken together, l -serine and glycine cause homocysteine-induced endothelial cell damage by reducing the level of intracellular homocysteine.l -Serine acts by competitively inhibiting homocysteine uptake in the cells. However, the mechanism(s) by which glycine lowers homocysteine levels are unclear. Graphical abstract: Highlights: l -Serine and glycine ameliorated cell viability and apoptosis induced by homocysteine. l -Serine reduced homocysteine-induced ER stress by inhibiting homocysteine uptake. Glycine decreased intracellular homocysteine level and attenuated homocysteine-induced ER stress.